2013
DOI: 10.1016/j.addr.2012.07.014
|View full text |Cite
|
Sign up to set email alerts
|

Nanotopography-guided tissue engineering and regenerative medicine

Abstract: Human tissues are intricate ensembles of multiple cell types embedded in complex and well-defined structures of the extracellular matrix (ECM). The organization of ECM is frequently hierarchical from nano to macro, with many proteins forming large scale structures with feature sizes up to several hundred microns. Inspired from these natural designs of ECM, nanotopography-guided approaches have been increasingly investigated for the last several decades. Results demonstrate that the nanotopography itself can ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
274
1
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 354 publications
(283 citation statements)
references
References 312 publications
(354 reference statements)
1
274
1
1
Order By: Relevance
“…It is 57 therefore very important to be able to create nanostructured surfaces that are more biomimetic 58 compared to standard flat culture surfaces [2]. The recent developments of micro-and nano-59 fabrication technologies offer many possibilities for the application of nanostructured surfaces 60 in the fields of tissue engineering [3,4], medical prosthetics [5], biochips for diagnostics [6, 61 7], and cell microarrays [8]. 62…”
Section: Introduction 54mentioning
confidence: 99%
“…It is 57 therefore very important to be able to create nanostructured surfaces that are more biomimetic 58 compared to standard flat culture surfaces [2]. The recent developments of micro-and nano-59 fabrication technologies offer many possibilities for the application of nanostructured surfaces 60 in the fields of tissue engineering [3,4], medical prosthetics [5], biochips for diagnostics [6, 61 7], and cell microarrays [8]. 62…”
Section: Introduction 54mentioning
confidence: 99%
“…[11,12] However, conventional hydrogels lack the high mechanical performance and ordered structures of biological soft tissues such as cartilages and muscles. [13][14][15][16] In recent years, the mechanical performance of conventional hydrogels has been enhanced by optimizing polymer networks. [17][18][19][20][21][22] For instance, a double-network hydrogel with outstanding mechanical strength was reported by Gong et al This hydrogel contained a brittle polyelectrolyte as the first network and a flexible neutral polymer as the second network and exhibited a high elastic modulus (0.1-1.0 MPa) as well as high toughness values.…”
mentioning
confidence: 99%
“…Many biological soft tissues in nature, such as cartilage, skeletal muscles, corneas, and blood vessels, are natural hydrogel materials that exhibit anisotropic mechanical performances due to their highly ordered hierarchical nanocomposite structures. [13,26] From molecular assemblies to highly aligned extracellular fibrils and cells, a multilevel ordered hierarchy in these biological soft tissues is crucial for their biological function. [13,26,27] For example, skeletal muscles act as core actuation systems; in these muscles, collagen self-assembles into 1D fiber bundles, and these bundles gather directionally.…”
mentioning
confidence: 99%
“…To respect anisotropic organization of cardiac tissue and promote development of a functional cardiac syncytium, the fibrous structure needs to be aligned. Several studies demonstrated that the presence of aligned surface facilitates the orientation and organization of CMs [36] [37]. Moreover, high surface-to-volume ratio and porosity are indispensable elements for the migration of cells and vascularization.…”
Section: Polymeric Scaffold Characteristics For Cardiac Tissue Enginementioning
confidence: 99%